Analysis of Ship Waiting Time to Get Shipyard Service at PT. Dokp And Shipping Waiame in Ambon City - Husnyati Kiat (Indo-Fintech Intellectuals: Journal of Economics and Business, 2021)
The purpose of this research is to determine the best service system that can be applied by PT. Dokp and Shipping Waiame Ambon. so that the waiting time can be pressed. This research is descriptive research, with the population in this study is the entire number and type of ships that have docked at PT. DOKP and Waiame shipping for 13 months. The sampling method used in this research is Convenience Sampling. The sample used in this study is the number of ships repaired in a period of up to 13 months. The analysis tool used is queueing theory of multi channel-single phase model. The results showed that the average arrival rate of ships per month is as many as 9 units of ships, while the average length of docking as much as 3 units of ships per month. Therefore, it can be seen that the level of service is not optimal to reduce the arrival rate of ships, and the chance of idleness by 2. Therefore, the arrival of ships is more than the level of ship service at PT. Dokp and Shipping Waiame Ambon.